Faktor penentu keputusan pembelian konsumen pada produk Wiu Bakery - Nugrohowati, Dwi; Pahlevi, Reza Widhar (Academy of Education Journal, 2024)
This research aims to determine the determining factors that influence purchasing decisions for Wiu Bakery products, namely those consisting of price, product quality and brand image variables. This research uses a convenience sampling technique or sampling by taking samples that are easy to find. Questionnaires were distributed to Wiu Bakery consumers from sales data of 50 consumers, but 41 respondents returned the questionnaire and were suitable for processing. The analysis tool uses multiple linear regression analysis. The research results show that price and brand image have a positive influence on purchasing decisions for Wiu Bakery products. However, product quality does not influence the decision to purchase Wiu Bakery products